Integrated metabolomic and transcriptomic analysis reveals the biosynthesis mechanism of dihydrochalcones in sweet tea (Lithocarpus litseifolius) - Ling, Shaojun; Lin, Qiongqiong; Zhou, Biaofeng; Liang, Yiye; Luo, Wenji; Shen, Zhao; Wang, Jingshu; Niu, Jingwei; Qiao, Liangjing; Wang, Baosheng; Liu, Hui (Frontiers in Plant Science, 2025)
The demand for plant-based, low-calorie natural sweeteners is increasing. Four dihydrochalcones (DHCs), namely phloretin, phlorizin, trilobatin, and sieboldin, have been identified in the leaves of Lithocarpus litseifolius. These compounds serve as natural flavor sweeteners with potential health-promoting effects. However, the biosynthetic pathways of these DHCs are not yet fully understood. In this study, the content of four DHCs was quantified using LC-MS/MS across five developmental stages (S1–S5) of L. litseifolius leaves. Our results revealed an accumulation pattern where DHC levels peaked at stage S3, followed by a sharp decrease at stages S4 and S5, with the exception of sieboldin, which maintained high levels. We elucidated the complete biosynthetic pathway of DHCs, involving 82 candidate enzyme-encoding genes, including five PALs, three C4Hs, 13 4CLs, 18 CDBRs, five CHSs, 14 P2’GTs, 12 P4’GTs, nine F3’Hs, and three CH3Hs, and found that either tandem duplication or proximal duplication may have contributed to the expansion of key genes such as CDBR, P2’GT, and P4’GT. Furthermore, we reconstructed 11 regulatory networks of DHCs, two modules were positively related to the contents of phloretin, phlorizin, and trilobatin (r = 0.54–0.69, P < 0.05), while two other modules were associated with sieboldin accumulation (r = 0.59–0.74, P < 0.05). We also identified MYB, WD40-like, WRKY, and bHLH transcription factors as potential regulators in the biosynthesis of four DHCs. We found two biosynthetic gene clusters of DHCs, including nine and four genes encoding CDBR and P2’GT, respectively. Syntenic and phylogenetic analyses revealed that these two BGCs may have experienced independent evolutionary processes within the Fagaceae family. Our study provides a theoretical foundation for the resource development and utilization of sweet tea. It also paves the way for the development of high-quality natural sweeteners.